An Evaluation of Hand Dominancy and its Relationship with Hand involvement and hand Dexterity in Patients with Rheumatoid Arthritis - Ebru UMAY,; Alev ÇEVİKOL,; Aytül ÇAKCI, (Archives of Rheumatology, 2013)
Objectives: This study aims to evaluate whether hand dominancy in patients with rheumatoid arthritis (RA) using their right hand dominantly is associated with clinical and radiological involvement of the hand and hand dexterity. Patients and methods: Two hundred and forty-nine patients (238 females, 11 males; mean age 53.0±11.8 years; range 25 to 78 years) with right-hand dominance were included in this study. In the evaluation of hand and wrist involvement in the patients, the range of motion (ROM) of the wrist, metacarpophalangeal joints (MCPJs) and proximal interphalangeal joints (PIPJs) were measured and the presence of deformities and tenosynovitis was recorded. Hand dexterity was assessed using the nine hole peg test, hand grip capacity (six types), and grip strength. The Larsen score was calculated, the results were compared between two hands. Results: Range of motion limitation in wrist flexion, extension and total number of PIPJs, piano key sign, and boutonniere deformity were more common in the dominant (right) hand. The right hand was stronger than the left; however, there was no difference between the hands in terms of their grip types. The radiological findings of the right hand were more destructive than those of the left hand. Conclusion: Our study results suggest that patients with RA have a higher incidence of joint limitation and radiological damage in the dominant hand and some deformities can be observed more frequently in the dominant hand. However, the dominant hand is still stronger than the non-dominant hand.